PSYCHOSOCIAL PROBLEM OF PATIENTS WITH CHRONIC HEART FAILURE: A MODERN VIEW ON INPATIENT TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article presents the results of the analysis of the psychoemotional state of patients with CHF, with an emphasis on the impact of anxiety-depressive symptoms on their quality of life. The relationship between the severity of emotional disorders and the severity of heart failure is described.